Fixação de arsênio em resíduos da mineração de ouro: mecanismo e aplicação - Fernando Luiz Pantuzzo (2008)
The aim of the present work was to investigate arsenic association, mineralogy and potential mobility from industrial residues and synthetic metallic arsenates. Samples of industrial residues collected in a gold extraction plant have been initially used. They were disposed during a period between one and two decades. Arsenic was shown to occur as As(V) species, predominantly in the form of amorphous iron arsenate (55 - 75 %Astotal) and sorbed onto amorphous iron oxi-hydroxides (20 - 37 %Astotal). Evidences of the presence of Ca-arsenate phases (indefinite composition) and Al-arsenate coprecipitation are provided. Gypsum (CaSO4.2H2O) was the predominant phase in the bulk residues, and its controlled leaching (via conductivity) with water resulted in a reduction of bulk mass as high as 70%, with potential arsenic release up to 3.5% Astotal. This amount corresponds to a maximum of 0.7g.kg-1 of potentially mobile arsenic. It was also observed a passive enrichment of iron in the oldest residues (14- 21 years), as well as a relative low concentration of Ca, S and As if compared to the more recent residues (7-14 years). These findings suggest that a process of remobilization, attributed to the dissolution of a Ca-arsenate phase (e.g. CaHAsO4.H2O) and a fraction of gypsum (formed during As precipitation from the process effluent process), took place along the two decades. The present enriched iron concentration (Fe/As= 6.0 currently vs. 0.4 in the effluent treatment) also suggest an increased arsenic stability for the oldest residues, if compared with the most recent ones (7 to 14 years old). Structural transformations of the amorphous co-precipitates into more ordered phases were not identified, even after 21 years of disposal. The Alarsenate association in the industrial coprecipitates motivated the investigation of solubility of an amorphous aluminum arsenate phase synthesized in laboratory. Under conditions of congruent dissolution (pH = 2.7), a Ksp value of 10-17.9 ± 0.07 at 25°C was determined for the compound with the chemical formula AlAsO4.3.4H2O. In order to better understand the mechanism of arsenic immobilization, Fe(III)-As(V) materials were also synthesized at different pH conditions (1.5, 4, 6 and 8) and Fe/As molar ratios (1:1, 2:1 and 4:1). The sample formed at pH 1.5 (Fe/As=1:1) was characterized as FeAsO4.1.8H2O. In the samples produced from Fe/As=4 solutions, arsenic was found to coprecipitate with ferryhydrite or schwertmannite, the latter in the presence of sulfate. The specifically sorbed arsenic was evaluated through selective leaching with phosphate solution. The sorbed arsenic increased with the pH increase (changing from 6% Astotal at pH 6 to 85% Astotal at pH 8) and was little affected by the increase of Fe/As molar ratio (from 1:1 to 4:1) staying between 20% and 25% Astotal. The analyses of the products formed during the partial thermal decomposition of the amorphous materials, allowed to infer the increase of amount of ferryhydrite with the increase of pH. The increase of the Fe/As molar ratio led to the presence of amorphous hydrated phases with Fe/As=2 and 3, in addition to the presence of amorphous FeAsO4.xH2O, ferrihydrite and schwertmannite (in sulfate media, pH4).The overall results allow us to conclude that the highest and lowest arsenic removal can not be correlated to the predominance of adsorption or precipitation mechanisms. It is rather correlated with the nature of the precipitate formed during the removal process. Furthermore, the longterm behavior of the slimes confirms the participation of mechanisms, adsorption and coprecipitation, as well as the prevailing role of iron in the immobilization of arsenic in mining sites.